Proceedings of the 8th International Conference on Civil Engineering - Feng, Guangliang (Lecture Notes in Civil Engineering, 2022)
This open access book is a collection of accepted papers from the 8th International Conference on Civil Engineering (ICCE2021). Researchers and engineers have discussed and presented around three major topics, i.e., construction and structural mechanics, building materials, and transportation and traffic. The content provide new ideas and practical experiences for both scientists and professionals.